NATO and the European Union - Archick, Kristin; Gallis, Paul E.; Library of Congress. Foreign Affairs Division. (Library of Congress. Congressional Research Service., 2006)
Report which discusses issues related to the North Atlantic Trade Organization (NATO) and the European Union (EU) including the level of involvement of the entities in using political and military actions to defend against terrorism and proliferation, the types of military forces necessary, the role of the EU in crisis management, the appropriateness of decision-making procedures to respond to emerging threats, and the role of other international institutions.